Comparison of the NRECA and FJ Mock Methods for Raw Water Availability on a Very Small Island, Karimunjawa - Azkiya, Nurul Azka; Hartono, Hartono; Robial, Siti Muawanah (Universitas Pendidikan Nasional, 2025)
Karimunjawa Island, as one of the very small islands in Indonesia, faces serious challenges in meeting raw water needs due to limited surface water resources and high evaporation rates. Evaluating water availability is essential to support the needs of the local population and the tourism sector. This study aims to compare two methods of estimating raw water availability, namely the NRECA and FJ Mock methods, using data on rainfall, climatology, hydrology, geography, topography, population, vegetation, evapotranspiration, and infiltration. The analysis results show that the NRECA method produces a maximum discharge of 0.726 m³/s in January and a minimum discharge of 0.000 m³/s in August. Meanwhile, the FJ Mock method yields a maximum discharge of 0.927 m³/s in December and a minimum discharge of 0.004 m³/s in August. In addition to the analysis results, this journal also presents sample calculations using both methods. Based on the findings, the NRECA method is considered more suitable for application in small island areas with limited data and complex hydrogeological conditions.